Hallmarks of a genomically distinct subclass of head and neck cancer - Muijlwijk, Tara; Nauta, Irene H.; van der Lee, Anabel; Grünewald, Kari J. T.; Brink, Arjen; Ganzevles, Sonja H.; Baatenburg de Jong, Robert J.; Atanesyan, Lilit; Savola, Suvi; van de Wiel, Mark A.; Peferoen, Laura A. N.; Bloemena, Elisabeth; et al. (Nature communications, 2024)
Cancer is caused by an accumulation of somatic mutations and copy number alterations (CNAs). Besides mutations, these copy number changes are key characteristics of cancer development. Nonetheless, some tumors show hardly any CNAs, a remarkable phenomenon in oncogenesis. Head and neck squamous cell carcinomas (HNSCCs) arise by either exposure to carcinogens, or infection with the human papillomavirus (HPV). HPV-negative HNSCCs are generally characterized by many CNAs and frequent mutations in CDKN2A , TP53 , FAT1, and NOTCH1 . Here, we present the hallmarks of the distinct subgroup of HPV-negative HNSCC with no or few CNAs (CNA-quiet) by genetic profiling of 802 oral cavity squamous cell carcinomas (OCSCCs). In total, 73 OCSCC (9.1%) are classified as CNA-quiet and 729 as CNA-other. The CNA-quiet group is characterized by wild-type TP53 , frequent CASP8 and HRAS mutations, and a less immunosuppressed tumor immune microenvironment with lower density of regulatory T cells. Patients with CNA-quiet OCSCC are older, more often women, less frequently current smokers, and have a better 5-year overall survival compared to CNA-other OCSCC. This study demonstrates that CNA-quiet OCSCC should be considered as a distinct, clinically relevant subclass. Given the clinical characteristics, the patient group with these tumors will rapidly increase in the aging population. HPV-negative head and neck squamous cell carcinomas (HNSCCs) are generally characterized by many copy number alterations (CNAs) and mutations. Here, the authors characterize a subgroup of HPV-negative HNSCC with no or few CNAs (CNA-quiet) by genomic profiling of 802 oral cavity squamous cell carcinomas.